Public Space as Resistance: Kaltim Kamisan and Indonesia’s Democratic Restrictions (JED (Jurnal Etika Demokrasi), 2026)
This study is motivated by the narrowing of civic space in Indonesia, where constitutional guarantees of freedom of expression increasingly encounter administrative, spatial, and political restrictions in practice. This study aims to analyze how public space is utilized as a form of civil society resistance through Aksi Kamisan East Kalimantan in responding to democratic restrictions. Using a qualitative descriptive case study approach, the research was conducted in Samarinda, East Kalimantan, through direct observation, documentation, and semi-structured in-depth interviews with five purposively selected informants consisting of movement organizers, participants, and an academic observer. Data were analyzed using interactive and thematic analysis grounded in Gramsci’s theory of hegemony and counter-hegemony. The findings show that Aksi Kamisan East Kalimantan utilizes Tepian Mahakam and the East Kalimantan Governor’s Office as strategic arenas for articulating human rights, environmental, indigenous, and social justice issues through peaceful symbolic actions. The movement faces administrative control, intimidation, limitations on public expression, digital attacks, and disruption of protest infrastructure, yet it transforms public space into a site of political education, collective memory, and participatory democratic engagement. This study concludes that public space functions as a contested arena where civil society negotiates, resists, and reclaims democratic participation amid local restrictions. The novelty of this study lies in positioning public space as a localized counter-hegemonic arena shaped by socio-environmental conflicts and democratic constraints in East Kalimantan. The study contributes theoretically to debates on democracy, public space, and social movements, while practically emphasizing the importance of inclusive public spaces in strengthening participatory democracy.